Design and modeling of PCB coils for inductive power charging. Issue 2 (13th November 2015) - Vigneau, Guillaume; Cheikh, Mohamed; Benbouhout, Rachid; Takacs, Alexandru
Abstract : This article presents a modeling and parametric investigation of printed circuit board (PCB) coils used in inductive power charging systems by using intensive full-wave electromagnetic simulations. Low frequencies applications (below 1 MHz) are targeted. The proposed modeling approach and design methodology are validated for wireless power transfer systems including transmitting (Tx) and receiving (Rx) coils. The impact of ferrite materials used for shielding and efficiency improvement is also analyzed. Optimized PCB coils allowing a theoretical efficiency of 88.7% at 100 kHz and 98.5% at 1 MHz confirms that PCB coils are appropriate for wireless power transfer at such frequencies.